Students’ Perceptions of Teaching Quality: Validation of the teaCh Scale in a Sample of Croatian Upper Secondary School Students - Krešimir Jakšić; Irena Burić (Psychological Topics, 2025)
Teaching quality is an important construct related to students’ affective and cognitive outcomes. However, it is usually measured with instruments that lack a clear theoretical background and/or whose psychometric properties have not been tested with appropriate statistical procedures such as multilevel modeling. Recently, Wisniewski et al. (2020) developed the teaCh scale, which measures the quality of teaching based on the students’ perceptions of seven dimensions: Care, Control, Clarity, Consolidation, Conferment, Challenge, Captivation. The aim of the study was to further test the psychometric properties of this scale using a large sample of upper secondary school students in Croatia. The results of the study show that the seven factors have adequate predictive validity for task value, student self-efficacy, and final grade, as well as adequate convergent validity and reliability. However, there are strong intercorrelations between the dimensions. These results confirm that measuring teaching quality through student reports is challenging from a psychometric point of view, but that students’ perceptions can still provide useful feedback for teachers.